Hookworm infection still prevalent in the less developed urban area in jakarta, Indonesia - Sem S. Surja; Soegianto Ali; Clara Ajisuksmo; Herry Pramono; Nilla S.D. Iustitiani; Celine; Cindy (Elsevier, 2021)
Objective: Soil-transmitted helminth (STH) infections is prevalent in some areas in Indonesia. We predicted that there are few urban area hotspots, especially in the less developed urban area. This study aimed to determine the prevalence of STH infection in children and its association with environmental factor in Jakarta's less developed urban area. Methods: This observational study took place in the slum area of Pluit and Penjaringan, North Jakarta. Stool samples were taken from children of under 5 years old. Duplicate methods of Kato-katz and Harada Mori were used to identify eggs or larvae of STH in the stools. Environment condition, personal toilet ownership was also documented and studied by using questionnaire based interviews. Results: A total of 158 stool samples were collected and examined. Seventeen samples (10.76%) were positive for STH infection. One sample had a high number of Ascaris lumbricoides' eggs (7.824 eggs/gram stool). Using Harada Mori methods, 16 samples with positive filariform larvae of hookworm were found. The data from our survey suggested that the environment's factor and sanitation play a major role in STH life cycle. Conclusion: The incidence of STH infections in the two less developed urban areas are still above national goals. The most prevalent STH infection is the hookworm. Environmental factor seems to have contribution in STH's transmission. A policy review on diagnostic methods and management of STH infections in Indonesia is needed, especially in the less developed urban areas.